Laccase enzymes: purification, structure to catalysis and tailoring - Moin, Syed Faraz; Omar, Muhammad Nor (Bentham Science Publishers, 2014)
Laccases belong to the multicopper binding protein family that catalysis the reduction of oxygen molecule to produce water. These enzymes are glycosylated proteins and have been isolated and purified from fungi, bacteria, plant, insects and lichens. The variety of commercial and industrial application of laccases has attracted much attention towards the research addressing different aspects of the protein characterization, production and fit for purpose molecule. Here we briefly discuss the purification, catalytic mechanism in light of available understanding of structure-function relationship and the tailoring side of the protein, which has been the subject of recent research. Purification strategy of laccases is a method of choice and is facilitated by increased production of the enzyme. The structure-function relationship has given insights to unfold the catalytic mechanism. Site directed mutagenesis and other modification at C-terminal end or surrounding environment of copper centres have shown promising results to fit for purpose aspect, with a lot remains to be explored in glycosylation status and its alteration.